Securing the Internet's Routing Infrastructure. - Ortiz, Jr., Sixto (Computer (00189162), 2009)
The article discusses security for the Internet’s routing structure. A major problem is the ability of hackers to intercept or reroute Internet communication. The author’s examination of router security covers the basics of what Internet routers do, router vulnerabilities, and a discussion of several ongoing efforts at increasing router security including BGPSec technology, RPKI infrastructures, Secure BGP, and Secure Origin BGP. He concludes by acknowledging obstacles to greater use of routing-security methods. INSET: A VARIETY OF ROUTING ATTACKS.